Thermal discomfort in healthcare workers during the COVID-19 pandemic - Lembo, Marco; Vedetta, Carmela; Moscato, Umberto; del Gaudio, Michele (La Medicina del Lavoro, 2021)
Introduction: Due to the COVID-19 pandemic, healthcare workers are now required to use additional personal protective equipment (PPEs) to protect themselves against the virus. That led to an increased clothing insulation which is negatively affecting the perceived healthcare workers’ thermal sensation. Objectives: While demonstrating through software simulations the potential level of thermal discomfort healthcare workers involved in the COVID-19 emergency can be subjected to, this work aims at identifying measures to improve thermal sensation perception and acceptable thermal conditions for medical personnel. Methods: After having obtained the insulation values of individual clothing used by staff during COVID-19 emergency through the use of a thermal well-being evaluation software, the Fanger indexes (PMV - Predicted Mean Vote and PPD - Predicted Percentage of Dissatisfied) were calculated in order to estimate staff satisfaction to microclimatic conditions. Results: The use of COVID-19 additional PPEs with an air temperature equal to 22 °C (normally considered optimal) brings the PMV index equal to 0.6, which corresponds to 11.8 % being unsatisfied (PPD) due to perceived heat. Discussion: The use of additional protective devices significantly increases the clothing insulation level, facilitating the onset of conditions of thermal discomfort in the health workers. Workers engaged in the execution of nasopharyngeal swabs were most affected by the summer weather conditions and certainly represent the most critical category, for which it would be recommended to implement a higher turnover of service to reduce individual exposure time and consequent discomfort.